SYNTHESIS OF NICRALX MICROPARTICLES USING DRY MILLING AND WET MILLING PROCESSES - Ramandhany, Safitry; Triyono, Djoko; Sugiarti, Eni; Desiati, Resetiana Dwi; Sundawa, Risma Yulita (National Research and Innovation Agency (BRIN), 2023)
The characteristics of synthesized NiCrAlY and NiCrAlZr composite powders produced by the milling process were investigated to understand the particle size, the shape of particles, and the properties of crystalline structure. The milling process was carried out by combining dry milling with the wet milling method to prevent agglomeration, produce a homogeneous alloy powder, and reduce the particle size. Ethanol was used during the wet milling process as a process control agent. The PSA (particle size analysis) showed that the particle size was effectively reduced from ±70 μm to less than 30 μm. In addition, surface structure analysis characterized by SEM (scanning electron microscope) revealed that particle shape changed from blocky particles after dry milling into flaky, flattened, and fragmented particles after wet milling. An XRD (x-ray diffraction) was used to identify the phases of powders before and after the mechanical milling process. Crystal structure analysis was calculated from the change of peak broadening in XRD peak spectra. The Williamson-hall method has been performed to calculate the strain and crystallite size of synthesized NiCrAlY and NiCrAlZr composite powder in the present study. The findings in this study show the characteristics of powders, which are important information for producing coatings with good performance.